Pengaruh Kepercayaan Terhadap Kinerja Rantai Pasok Dimediasi Oleh Inovasi - Raihan Subakti; Moh. Mukhsin; Gerry Ganika (CV. ULIL ALBAB CORP, 2025)
This quantitative study investigates the influence of trust on supply chain performance, mediated by innovation, within the retread tire manufacturing industry in Greater Tangerang. The research addresses the observed inconsistencies in supply chain performance among producers, hypothesizing that trust and innovation play crucial roles. A total of 42 retread tire manufacturers in Greater Tangerang constituted the sample, selected using a saturation sampling method to ensure comprehensive representation of the population. primary data were collected through questionnaires and subsequently analyzed using SmartPLS 4. The findings several key insights. Firstly, trust was found to have a positive but not statistically significant effect on supply chain performance. This Suggests that while trust is beneficial, its direct impact on its own. Secondly, trust demonstrated a positive and significant influence on innovation, indicating that higher levels of trust among supply chain partners foster a more innovative environment. Thirdly, innovation itself had a positive and significant effect on supply chain performance, highlighting its direct contribution to operational improvements. This full mediation effect implies that trust primarily enhances supply chain performance indirectly, by stimulating innovation. These results underscore the critical importance of fostering both trust and innovation as interconnected strategies for optimizing supply chain efficiency and competitiveness in the retread tire industry. The findings several key insights. Firstly, trust was found to have a positive but not statistically significant effect on supply chain performance. This Suggests that while trust is beneficial, its direct impact on its own. Secondly, trust demonstrated a positive and significant influence on innovation, indicating that higher levels of trust among supply chain partners foster a more innovative environment. Thirdly, innovation itself had a positive and significant effect on supply chain performance, highlighting its direct contribution to operational improvements. This full mediation effect implies that trust primarily enhances supply chain performance indirectly, by stimulating innovation. These results underscore the critical importance of fostering both trust and innovation as interconnected strategies for optimizing supply chain efficiency and competitiveness in the retread tire industry.